Intensive Listening and Cutting-Edge Strategies Unlock Language Mastery - SARBUNAN, THOBIAS (Universitas Maritim Raja Ali Haji (UMRAH), 2024)
The primary objective of this research study is to examine the implications of intensive listening techniques on language acquisition and comprehension skills. The Research examines different methods, resources, and technology applications supporting successful language acquisition. The theoretical framework includes Krashen's Input Hypothesis and the Comprehensible Output Hypothesis, emphasising the crucial importance of authentic language input. Various platforms, such as podcasts, YouTube, and ELA resources, are crucial for establishing captivating and immersive language environments. There is a strong emphasis on the responsible integration of AI and technology in education, focusing on ensuring fairness and transparency. Implementing metacognitive strategies, problem-solving techniques, and learner autonomy are fundamental to successful intensive listening practices. Additionally, the study recognises the impact of native languages on language acquisition and considers educators' diverse responsibilities in promoting oral proficiency. The Research has identified several promising areas for further investigation, including neurocognitive correlates, intercultural communication, motivation, and technology integration. The study provides practical insights that can assist educators, curriculum developers, and language learning programs in creating engaging and genuine listening activities that promote linguistic proficiency and effective communication.